Morphological, immunohistochemical, and chromosomal analysis of multicystic chromophobe renal cell carcinoma, an architecturally unusual challenging variant - Foix, Maria Pané; Dunatov, Ana; Martinek, Petr; Mundó, Enric Condom; Suster, Saul; Sperga, Maris; Lopez, Jose I; Ulamec, Monika; Bulimbasic, Stela; Montiel, Delia Perez; Alaghehbandan, Reza; Peckova, Kvetoslava; et al. (Virchows Archiv, 2016)
Chromophobe renal cell carcinoma (ChRCC) is typically composed of large leaf-like cells and smaller eosinophilic cells arranged in a solid-alveolar pattern. Eosinophilic, adenomatoid/pigmented, or neuroendocrine variants have also been described. We collected 10 cases of ChRCC with a distinct multicystic pattern out of 733 ChRCCs from our registry, and subsequently analyzed these by morphology, immunohistochemistry, and array comparative genomic hybridization. Of the 10 patients, 6 were males with an age range of 50-89 years (mean 68, median 69). Tumor size ranged between 1.2 and 20 cm (mean 5.32, median 3). Clinical follow-up was available for seven patients, ranging 1-19 years (mean 7.2, median 2.5). No aggressive behavior was documented. We observed two growth patterns, which were similar in all tumors: (1) variable-sized cysts, resembling multilocular cystic neoplasm of low malignant potential and (2) compressed cystic and tubular pattern with slit-like spaces. Raisinoid nuclei were consistently present while necrosis was absent in all cases. Half of the cases showed eosinophilic/oncocytic cytology, deposits of pigment (lipochrome) and microcalcifications. The other half was composed of pale or mixed cell populations. Immunostains for epithelial membrane antigen (EMA), CK7, OSCAR, CD117, parvalbumin, MIA, and Pax 8 were positive in all tumors while negative for vimentin, TFE3, CANH 9, HMB45, cathepsin K, and AMACR. Ki67 immunostain was positive in up to 1 % of neoplastic cells. Molecular genetic examination revealed multiple chromosomal losses in two fifths analyzable tumors, while three cases showed no chromosomal numerical aberrations. ChRCC are rarely arranged in a prominent multicystic pattern, which is probably an extreme form of the microcystic adenomatoid pigmented variant of ChRCC. The spectrum of tumors entering the differential diagnosis of ChRCC is quite different from that of conventional ChRCC. The immunophenotype of ChRCC is identical with that of conventional ChRCC. Chromosomal numerical aberration pattern was variable; no chromosomal numerical aberrations were found in three cases. All the cases in this series have shown an indolent and non-aggressive behavior.
Keywords: oxyfilní adenom; nádory ledvin; Male; Multicystic; srovnávací genomová hybridizace; karcinom z renálních buněk; chromozomální aberace; Mucin-1; Kidney Neoplasms; Kidney; Diagnosis, Differential; Aged; imunohistochemie; mužské pohlaví; senioři; lidé středního věku; Chromophobe renal cell carcinoma; Chromosome Aberrations; senioři nad 80 let; lidé; ženské pohlaví; Immunohistochemistry; Humans; Comparative Genomic Hybridization; diferenciální diagnóza; Aged, 80 and over; mucin 1; ArrayCGH; Carcinoma, Renal Cell; Female; Adenoma, Oxyphilic; Biomarkers, Tumor; nádorové biomarkery; Middle Aged